Muslim worlds’ missed opportunity - Ameer Ali (Penerbit Universiti Kebangsaan Malaysia, 2018)
The longing to recapture the glorious past of Islam is almost universal in the Muslim world. An accurate diagnosis of failed experiences in the past and a methodology to exploit any emerging opportunities are essential to achieve this objective. An opportunity arose in the recent past that should have been thoughtfully utilised in this venture. How and why did the Muslim world squandered that opportunity and what are the consequences? Is a return to the past glory ever possible?